THE INFLUENCE OF SPORT INSTITUTIONIN PHYSICAL EDUCATION:: A LITERATURE REVIEW - Clayton Aves dos Santos, Anderson; Lucena de Andrade, Gilvaney; Adegilson da Silva Barbosa, Antonio (Health and Society, 2021)
Given the broad spread of sports in the school context, this study through a literature review, aims to analyze the influence of sports content in physical education classes, reflecting on the sport as one of the contents to be discussed in class physical education and not just the one, is often treated with. In order to rethink the sport in the school context, considering it as a content committed to the educational process (Neuenfeldt 2008), and encouraging teachers to take over the sport as one of the strategies in the teaching-learning of diverse knowledge (conceptual, procedural and attitudinal), contributing and complementing it with the other major areas (game, fight, dance, gymnastics) in physical education to foster meaningful learning the learner.